2019
DOI: 10.3390/ijms20051042
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Ovarian Cancer Cells Overexpressing CD44 with Immunoliposomes Encapsulating Glycosylated Paclitaxel

Abstract: Paclitaxel (PTX) is one of the front-line drugs approved for the treatment of ovarian cancer. However, the application of PTX is limited due to the significant hydrophobicity and poor pharmacokinetics. We previously reported target-directed liposomes carrying tumor-selective conjugated antibody and encapsulated glycosylated PTX (gPTX-L) which successfully overcome the PTX limitation. The tubulin stabilizing activity of gPTX was equivalent to that of PTX while the cytotoxic activity of gPTX was reduced. In huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 36 publications
0
18
0
2
Order By: Relevance
“…In addition, the anti-CD44 mAb A3D8 enhanced apoptosis in acute myeloid leukaemia cells through caspase-8 activation by binding to CD44s protein [ 210 ]. In human ovarian cancer cell lines overexpressing CD44, the encapsulated glycosylated paclitaxel liposomes (gPTX-L) conjugated with anti-CD44 antibody efficiently enhanced cytotoxicity in vitro and in vivo, suppressing tumour growth in vivo [ 211 ].…”
Section: Targeting Cd44: a Promising Cancer Therapeutic Strategymentioning
confidence: 99%
“…In addition, the anti-CD44 mAb A3D8 enhanced apoptosis in acute myeloid leukaemia cells through caspase-8 activation by binding to CD44s protein [ 210 ]. In human ovarian cancer cell lines overexpressing CD44, the encapsulated glycosylated paclitaxel liposomes (gPTX-L) conjugated with anti-CD44 antibody efficiently enhanced cytotoxicity in vitro and in vivo, suppressing tumour growth in vivo [ 211 ].…”
Section: Targeting Cd44: a Promising Cancer Therapeutic Strategymentioning
confidence: 99%
“…Many studies demonstrated that systemic delivery of paclitaxel using a nanocarrier or receptor resulted in a significantly improved antitumor response. 108,157 For example, paclitaxel derivative-loaded nanoparticles showed lower cytotoxicity toward bone marrow-derived macrophages (BMDMs) than free paclitaxel, up-regulating the CD11b expression in BMDMs. This nanoparticle polarized macrophages toward M1 and inhibited their M2 dif-ferentiation, both on phenotypic and functional levels.…”
Section: Paclitaxelmentioning
confidence: 99%
“…Therefore, many vectors have been used to study the reduction of paclitaxel toxicity. Many studies demonstrated that systemic delivery of paclitaxel using a nanocarrier or receptor resulted in a significantly improved antitumor response 108,157 . For example, paclitaxel derivative‐loaded nanoparticles showed lower cytotoxicity toward bone marrow‐derived macrophages (BMDMs) than free paclitaxel, up‐regulating the CD11b expression in BMDMs.…”
Section: Molecular Mechanisms On Natural Products In Tumor Immunotherapymentioning
confidence: 99%
“…Standard histological analyses showed that SIL-treated rats exhibited numerous granulomas, whereas the livers of SSIL2-treated animals exhibited only a few isolated granulomas. Khayrani et al 39 assessed the therapeutic efficacy of glycosylated paclitaxel (gPTX)-loaded liposomes functionalized with anti-CD44 antibody (gPTX-IL). The in vitro cytotoxicity of gPTX-IL was tested in SK-OV-3 and OVK18 ovarian cancer cell lines.…”
Section: Antibodiesmentioning
confidence: 99%